FATTY ACID PROFILES OF CYCLOPOID COPEPOD NAUPLII Apocyclops panamensis AND THE EFFECTS OF SALINITY CHANGE - Gede S. Sumiarsa; Ronald P. Phelps (Indonesian Aquaculture Journal, 2007)
Lipid and fatty acid profiles were described for copepod nauplii Apocy clops panamensis from fertilized brackish water ponds, and after being acclimated to fullsea water salinity. Mean total lipid content of copepod nauplii collected from ponds fertilized with inorganic fertilizer combined either with alfalfa meal, rice bran, wheat bran, and a combination of these fertilizers ranged from 5.66 ± 0.15 to 7.76% ± 0.27%. Non-polar (neutral) lipid fraction of pond copepod nauplii was a significantly higher percentage of the total lipid content (74.5 ± 1.8 - 93.5% ± 1.0%) compared to those of polar lipid (6.5 ± 1.0 - 21.3% ± 1.8%) (P= 0.000). DHA/EPA ratio in neutral lipids ranged from 1.8 ± 0.2 - 2.0 ± 0.1 with no significant differences in three fertilization regimes. DHA was 27.5% ± 0.56% of the neutral lipids and EPA 14.8% ± 0.8%. Acclimation of copepod nauplii for six hours from brackish to full-sea water salinity reduced their lipid content and individual dry weight significantly. Mean total lipid content was reduced 44.2%, non-polar lipid was reduced 46.9% and polar lipid was reduced 24.4%.Acclimation altered the DHA/EPA ratio, in the neutral fraction the ratio increased 26.3% but in the polar fraction it decreased 25%.